Wicked charms ebook - Evanovich, Janet (Lizzy & Diesel, 2015)
NEW YORK TIMES BESTSELLER • Lizzy and Diesel are back in a wicked adventure from Janet Evanovich and Emmy Award–winning co-author Phoef Sutton.   Before he was murdered and mummified nearly a century ago, notorious bootlegger Collier “Peg Leg” Dazzle discovered and re-hid a famous pirate’s treasure somewhere along the coast of New England. A vast collection of gold and silver coins and precious gems, the bounty also contains the Stone of Avarice—the very item reluctant treasure seeker Lizzy Tucker and her partner, Diesel, have been enlisted to find. While Lizzy would just like to live a quiet, semi-normal life, Diesel is all about the hunt. And this hunt is going to require a genuine treasure map and a ship worthy of sailing the seven seas . . . or at least getting them from Salem Harbor to Maine.   Greed is eternal and insatiable, and Lizzy and Diesel aren’t the only ones searching for the lost pirate’s chest. People who have dedicated their entire lives to finding it are willing to commit murder or make a deal with the devil just to hold the fortune in their hands. One of those people may even be Wulf, Diesel’s deceptively charming and enigmatic cousin. Wulf desires the Stone of Avarice. He also desires Lizzy. It’s hard to say how far he’s willing to go to gain either one.   Wicked Charms is a swashbuckling adventure full of raiders, monkeys, minions, and mayhem. Lizzy and Diesel are going to have to do everything they can to keep their heads above water and hope they’re living a charmed life.